70-letie ugolovnogo rozyska . 70-letie ugolovnogo rozyska . 70th Anniversary of the Criminal Investigation . 70-летие уголовного розыска - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussions, news coverage, and songs devoted to the 70th Anniversary of the Soviet Criminal Investigation. Дискуссия, репортажи и песни, посвященные 70-летию уголовного розыска СССР.